Exploitation of a technique in arranging an Islamic funeral - Syarilla Iryani, A. Saany; Julaily Aida, Jusoh; Engku Ahmad Zaki, Engku Alwi; Ahmad Nazari, Mohd Rose; Yousef A. Baker, El-Ebiary (2021)
Technologies continue to evolve and develop as practically all activities and services such as commerce, business, and online education can be terminated. Tragically, the commemorative service track and the handling service still run a similar cycle as more seasoned individuals have done previously. Here, the recommended app will help customers deal with the memory service faster and easier. The term "Islam"means identification with God and man, and complete surrender to God in contemplations, sayings, beliefs, and activities. Longitude in Islamic culture is sufficient and seen as a typical piece of life. Muslims consider that change begins with one country and then another, not an end. A Muslim's corpse is referred to in Arabic as a "burial service."I-JenzCare is a stage where service providers and customers can coordinate their needs in serving the remembrance service plan. I-JenzCare is a unique idea on the basis that no similar application or framework has been established regarding dealing with Islamic burial services in Malaysia yet. This research introduces new characteristics of the traditional Islamic burial service services practiced in the Malay community. I-JenzCare uses an innovative Analytic Hierarchy (AHP) that requires only a mid-end cell phone to keep everything according to the best customer experience principles. To illustrate this, the framework is a useful application for individuals who need immediate assistance in dealing with burial services in Malaysia.